PENGARUH PENAMBAHAN KAPUR TERHADAP KUAT TEKAN BEBAS PADA TANAH LEMPUNG - Martini, RA Sri; Oemiati, Nurnilam; Agusri, Erny; Yendi, Yendi (Universitas Muhammadiyah Palembang, 2024)
Clay soil subgrades have high pore water characteristics, which is a unique problem for civil structures such as buildings and road pavements. Lime contains compounds such as the element Calcium Oxide (CaO) of 79.43%. In reaction with clay minerals or other minerals, lime forms a strong calcium silicate gel that binds to soil particles. Different types of lime mixtures used are 0%, 12%, 15%, and 18% to soil weight with 28 days of soaking for four (4) days. From the two tests that have been carried out, namely soil compaction (Standard Proctor) and UCS (Unconfined Compression Streght) Soaked and Unsoaked, the optimum values obtained in soil compaction (Standard Proctor) and UCS (Unconfined Compression Streght) Soaked and Unsoaked are in the variation of soil addition + 18%. In the soil compaction test (Standard Proctor), the dry volume weight was 1.744 gr/cm3 and the optimum moisture content value was 16.03% and in UCS (Unconfined Compression Streght) Soaked the largest Qu value was 1.116 kg/cm2, and UCS (Unconfined Compression Streght) Unsoaked the largest Qu value was 2.714 kg/cm2.